Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.219
|View full text |Cite
|
Sign up to set email alerts
|

Image-Chat: Engaging Grounded Conversations

Abstract: To achieve the long-term goal of machines being able to engage humans in conversation, our models should captivate the interest of their speaking partners. Communication grounded in images, whereby a dialogue is conducted based on a given photo, is a setup naturally appealing to humans (Hu et al., 2014). In this work we study large-scale architectures and datasets for this goal. We test a set of neural architectures using state-of-the-art image and text representations, considering various ways to fuse the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…We augment Transformer sequence to sequence (seq2seq) networks on the encoder side with KIF to improve generative dialog models. We experiment on two dialog tasks, Wizard of Wikipedia and Engaging ImageChat (Shuster et al, 2020). In both datasets, models must leverage information external to the dialog history alone-in Wizard of Wikipedia, the chat requires access to knowledgeable facts and in Engaging ImageChat, discussion about a specific image.…”
Section: Kif For Generative Dialogmentioning
confidence: 99%
See 4 more Smart Citations
“…We augment Transformer sequence to sequence (seq2seq) networks on the encoder side with KIF to improve generative dialog models. We experiment on two dialog tasks, Wizard of Wikipedia and Engaging ImageChat (Shuster et al, 2020). In both datasets, models must leverage information external to the dialog history alone-in Wizard of Wikipedia, the chat requires access to knowledgeable facts and in Engaging ImageChat, discussion about a specific image.…”
Section: Kif For Generative Dialogmentioning
confidence: 99%
“…Agents are assigned one of 215 personalities (e.g., sweet, caring, excited) to increase engagingness. Previous work (Shuster et al, 2020 identified that both crowdworkers and models, when provided with personalities, produced more diverse, interesting responses, as evaluated by humans.…”
Section: Engaging Imagechatmentioning
confidence: 99%
See 3 more Smart Citations